The impact of global crisis on innovation and succession on family business from a socioemotional wealth perspective - WONG, Lai Kuan Kim (Institutional Knowledge at Singapore Management University, 2021)
The ongoing pandemic provides an invaluable opportunity to observe family businesses under extenuating circumstances, especially the Circuit Breaker which forced all non-essential workplaces to close to curb the spread of COVID-19; this in effect mandated that everyone should work from home. (Ministry of Health Singapore, 2020). This meant that for those working in intergenerational family businesses, they could also be living and working in the same confined space for an extended period. Does the accumulation of these circumstances create a phenomenon that leads to interactions that generate innovation and renew family bonds leading to succession? Family businesses are known to be motivated and committed to the preservation of socioemotional wealth (Miller & Le Breton-Miller, 2014). This study is keen on understanding the influence of a crisis on any gaps or overlaps in between each’s generations notion of socioemotional wealth and how this gap or overlap affects innovation and succession in family businesses. Past research has shown that the succession period can be a threat to family businesses but also an opportune time for innovation. Transgenerational entrepreneurship is a way for FBs to pursue innovation practices that improve entrepreneurship and to overcome the succession challenge. Building on transgenerational entrepreneurship research, the proposed family transgenerational entrepreneurship theory explains how intergenerational family businesses overcome generational gaps through the lens of socioemotional wealth to achieve succession and innovation before and during a crisis. Semi-structured interviews were conducted with privately owned family business owner/founder and potential successors respectively to investigate the impact of the crisis on innovation and succession in intergenerational family businesses. The proposed family transgenerational entrepreneurship theory extends our understanding of the implicit succession process within private intergenerational family businesses and the methods deployed to build intergenerational foundations that overcome conflict and promote intergenerational collaboration. This study expects to provide intergenerational family businesses clarity and handles to promote innovation and succession success and researchers a novel way of a examining the interaction and effects of individual intergenerational socioemotional wealth dimensions.